Evaluation of health surveillance activities of hajj 2013 in the hajj embarkation Palangkaraya - Hoesea, Elvan Virgo (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTMeningococcal meningitis and MERS-CoV is a disease that can be transmitted to a wary pilgrim considering the high incidence of both diseases in the Middle East region. This study was conducted to evaluate the surveillance activities conducted at embarkation Palangkaraya pilgrimage between 2013 and assess the surveillance activities based on the attributes of surveillance and barriers that occur in the implementation of activities. Experiment was conducted with descriptive design using quantitative approach. Questionnaires were completed at 6 implementing surveillance activities. Interviews were conducted to obtain information about the variables under study includes data collection, processing, analysis and interpretation, dissemination of information and surveillance attributes such as simplicity, flexibility, acceptability, sensitivity, positive predictive value, representatif, timeliness, data quality and data stability. Implementation health surveillance in the hajj embarkation Palangkaraya in 2013 showed all stages of the surveillance activities have been conducted in accordance with the procedures as well as evaluating surveillance activities in accordance attribute shows all the attributes of surveillance can be assessed, unless the sensitivity and positive predictive value because no cases of meningococcal meningitis. Conclusion that the implementation of health surveillance activities Hajj has been running quite well based approach to surveillance and surveillance attributes. The report has been used by the agency activities related to the activities of hajj embarkation. Need to increase the quantity and quality of manpower resources and facilitiesKeywords: disease transmission, hajj health surveillance, assessment attributes